SEEKING INTERSECTION OF RELIGIONS: An Alternative Solution to Prevent the Problem of Religious Intolerance in Indonesia - Chanifah, Nur; Mustapa, Arif (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Indonesia consisted of multiculture, ethnic and religion. There are six legal religions in Indonesia. Religious plurality is part of Indonesian life. In Religion, adherents always tried to compare between their own religion with other religions that can cause a truth claim of superiority of their religion. This caused any conflict like the case of GKI Yasmin in Bogor, three massive bomb blasts of Bali, and conflict of Ambon.  This is a library reseach applying sosiological approach. To analyze the problem, author used the conflict theory of Gillin and Gillin saying that conflict can be caused by deferences. Therefore, it is necessary to understand how the intersection of religions in order to prevent the conflict, included religious intolerence.  This research find that the intersection of religion can be found in values of humanity or the horizontal aspect (ḥabl  min al-nās). While the vertical aspect (ḥabl  min Allāh), they are different. By understanding the intersection of religions and nature of these differences, it is expected that religious harmony can be reinforced.***Indonesia terdiri dari beragam budaya, etnis dan agama. Terdapat enam agama yang diakui di Indonesia. Pluralitas tersebut merupakan bagian dari kehidupan masyarakat Indonesia. Pada kenyataannya, seseorang selalu ingin membandingkan antara agama mereka sendiri dengan agama-agama lain, sehingga yang dapat menyebabkan klaim kebenaran. Kondisi ini menyebabkan terjadinya konflik seperti kasus GKI Yasmin di Bogor, tiga bom Bali, dan konflik Ambon. Penelitian ini adalah penelitian kepustakaan dengan menggunakan pendekatan sosiologi. Analisis kajian menggunakan teori konflik Gillin dan Gillin yang menyatakan bahwa konflik dapat disebabkan oleh perbedaan. Oleh karena itu, perlu untuk memahami bagaimana titik pertemuan antar agama untuk mencegah konflik, termasuk intoleransi agama. Penelitian ini menemukan bahwa pertemuan agama dapat ditemukan dalam nilai-nilai kemanusiaan atau aspek horizontal (ḥabl  min al-nās). Sedangkan aspek vertikal (ḥabl  min Allāh), mereka berbeda. Dengan memahami pertemuan antar agama dan sifat perbedaan ini, diharapkan kerukunan beragama dapat diperkuat.